The Effect of Organizational Cynicism on Job Satisfaction Mediated by Spiritual Organization on ATC Employees at Soekarno Hatta Airport - Adristy, Janet Apta; Soelton, Mochamad (Journal of Sustainable Economic and Business, 2024)
Objective: This study aims to explore how cynicism, organizational spirituality, and the reciprocal relationship between these elements influence employee job satisfaction. Methodology: This study uses a quantitative approach with a survey method. The research data were taken from ATC employees at Soekarno-Hatta Airport. The research instrument was a questionnaire, which was then analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Findings: The results of the study revealed that organizational cynicism has a significant negative relationship with employee job satisfaction. However, this finding also shows that organizations can reduce the negative impact through efforts to build a positive organizational culture, as well as increasing spirituality in the organization. Conclusion: To overcome cynicism, organizations need to take strategic steps, such as strengthening communication, increasing transparency, and enforcing fairness in policies. These efforts can have a positive impact on overall employee job satisfaction.